Notes sur la géomorphologie d’une partie de la Côte de Beaupré - Sabourin, R.-J.-E. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1962)
Relief features of interest to the geomorphologist are numerous in the Québec City district. Among the more striking are the fault-line scarps at Montmorency Falls and on the island of Orléans and the various Champlain sea terraces among which Goldthwait's « 110-foot » and « Micmac » terraces are particularly well developed. A possible pre-Pleistocene section of the Montmorency river channel bas been suggested but still remains to be definitely established.